2018
DOI: 10.1101/405423
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inhibition of the Receptor for Advanced Glycation End-Products in Acute Respiratory Distress Syndrome: A Randomised Laboratory Trial in Piglets

Abstract: Background:The receptor for advanced glycation end products (RAGE) modulates the pathogenesis of acute respiratory distress syndrome (ARDS). RAGE inhibition was recently associated with attenuated lung injury and restored alveolar fluid clearance (AFC) in a mouse model of ARDS. However, clinical translation will first require assessment of this strategy in larger animals.Methods: Forty-eight anaesthetised Landrace piglets were randomised into a control group and three treatment groups. Animals allocated to tre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 51 publications
(72 reference statements)
0
8
0
Order By: Relevance
“…In a murine model of indirect lung injury, treatment with anti-RAGE antibody has been shown to abrogate lung damage and improve mortality, an effect likely related to mitigation of the RAGE-triggered pro-inflammatory signaling (45). Anti-RAGE therapies are currently being evaluated in human clinical trials for the treatment of chronic neurodegenerative disease and are actively being investigated for the treatment of acute sepsis and chronic inflammatory diseases (46)(47)(48)(49). It is plausible that anti-RAGE therapy may eventually have a role in patients with indirect lung injury and multiple organ dysfunction, especially among those patients with elevated sRAGE levels.…”
Section: Discussionmentioning
confidence: 99%
“…In a murine model of indirect lung injury, treatment with anti-RAGE antibody has been shown to abrogate lung damage and improve mortality, an effect likely related to mitigation of the RAGE-triggered pro-inflammatory signaling (45). Anti-RAGE therapies are currently being evaluated in human clinical trials for the treatment of chronic neurodegenerative disease and are actively being investigated for the treatment of acute sepsis and chronic inflammatory diseases (46)(47)(48)(49). It is plausible that anti-RAGE therapy may eventually have a role in patients with indirect lung injury and multiple organ dysfunction, especially among those patients with elevated sRAGE levels.…”
Section: Discussionmentioning
confidence: 99%
“…RAGE Inhibitors RAGE neutralization 1. RAGE inhibition (peptides, monoclonal antibodies, or soluble RAGE decoy receptors) restored lung function in acid instillation lung injury models in mice and in piglets [ 53 , 54 ] Endothelial/vascular dysfunction 1. Haptoglobin Scavengers of plasma-free hemoglobin 1.…”
Section: Therapies In Clinical Trials For Ardsmentioning
confidence: 99%
“…Plasma-soluble RAGE concentrations constitute a marker of epithelial lung injury, are increased in ARDS patients, and can predict ARDS development in ‘at risk’ patients [ 52 ]. RAGE appears to drive lung injury also, as evidenced by the finding that blockade of RAGE (using peptides, monoclonal antibodies, or soluble RAGE decoy receptors) reduced acid-induced lung injury in mice [ 53 ] and piglets [ 54 ].…”
Section: Therapies In Clinical Trials For Ardsmentioning
confidence: 99%
“…After three washes with PBS (1X), wounded cells were either left untreated (control) or treated with RAGE agonists alone or combined with RAP (12.5 µg/mL), before being incubated at 37°C with 95% humidified air and 5% CO2. The dose of RAP was chosen based on the findings from previous studies [29,[32][33][34]. The wound area was observed immediately after the scratch (h0) and 12, 24, and 48 h after treatment using a Nikon polarized optical microscope with 40x magnification and a digital camera body.…”
Section: In Vitro Model Of Alveolar Epithelium Wound Healing (Scratch...mentioning
confidence: 99%
“…Recent clinical and preclinical research has suggested that soluble RAGE (sRAGE) could be a biomarker of lung epithelial injury associated with severity and outcome in ARDS [19][20][21][22][23][24][25]. Moreover, RAGE inhibition or AGER gene deficiency decreased lung injury in animal models of experimental ARDS from both septic or non-septic causes [26][27][28][29]. Although the RAGE pathway has a major role in initiating and perpetuating nuclear factor-kappa B (NF-κB)mediated inflammation, it also contributes, among many other potential effects [11], to repair mechanisms such as peripheral nerve regeneration through the recruitment of axonal outgrowth pathways [14,30] or extracellular matrix synthesis and wound repair in human bronchial epithelial cells through stimulation by HMGB1 [31].…”
Section: Introductionmentioning
confidence: 99%